Eugenio Museum a Philippine folklore museum - Rulloda, Alfonse Rafael V.; Ozaeta, Emilio U. (Quezon City College of Architecture, University of the Philippines Diliman, 2016)
The thesis project entitled Eugenio Museum, named after Damaiana Eugenio, a former professor of the University of the Philippines Diliman and the so-called "Mother of Philippine Folk Literature", tackled the subject of Philippine Folklore, a part of Filipino culture that is not very popular in today's time. Philippine Folklore is about the Filipino Worldview. Knowing the Filipino Worldview is to help the Fllipino find their national identity for it contains the social knowledge of the world their ancestors had and used. The project established itself to promote the different Philippine Folk Literature and arts through a museum. The museum was chosen as the building type for its functions of preserving culture and heritage and it benefits to the tourism industry. After researching on similar establishments and on the thesis itself, consulting professors and museum curators, the main medium of the museum was video projections of the fold literature and viewing of artifacts and crafts of the indigenous people of the Philippines. The museum had rooms suitable for these medium while being integrated with other spaces such as administration offices, archive rooms and gift shops and museum cafes.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Museums